pengaruh latihan fisik (senam lansia) terhadap intensitas tidur lansia di UPT kesejahteraan sosial lanjut usia kupang - Lidia Gracella Koko Pau (CHMK NURSING SCIENTIFIC JOURNAL, 2019)
One of the problems experienced by the elderly is sleep disorders. This sleep disorder can affect the intensity of elderly sleep to be bad so that it can have an impact on the phisical and psychosocial of the elderly. The sleep disordered problem can solvable with physical exercise (elderly gymnastics). The purpose of the research to find out the effectiveness of physical exercise (elderly gymnastics) to the sleep intensity on the UPT. Kesejahteraan Sosial Lanjut Usia di Kupang.The signed used in this research was pre experiment used one group pretest-post test design approach. The independent variable in the research was physical exercise (elderly gymnastics) and the dependent variable was sleep intensity, the sample was gathered tottal sampling the resulted sample were 30 respondents and the data collected using questinnaire. The type of statistical test used in this research was wilcoxon test.Based on the resulted of wilcoxon test, the effect of physical exercise (elderly gymnastics) toward the the sleep intensity on the UPT. Kesejahteraan Sosial Lanjut Usia di Kupang, the statistical test resulted the value p = 0,000. Based on the resulted of the research can be concluded that there are effects of physical exercise (elderly gymnastics) toward elderly sleep intensity on the UPT. Kesejahteraan Sosial Lanjut Usia di Kupang. Than this physical exercise can be teach for elderly, so elderly can do the physical exercise by theirself everyday as the daily activity for increase the elderly sleep intensity.Keyword : Elderly, Physical Exercise, Sleep Intensity.